Україна : конфліктогенні фактори в умовах сучасного світового порядку - Глушков, В. О.; Glushkov, V. (My University, 2012)
In this article there is an analysis of the features of the Ukrainian geopolitical position influence on the development of its economic, political and legal systems. The basic directions of development of the international economic and political relations, and as a result, the place and the role of Ukraine in the contemporary world order. There is also an identification of a number of geopolitical factors, which may cause conflicts or acts of terror.
Глушков В. О. Україна : конфліктогенні фактори в умовах сучасного світового порядку / В. О. Глушков // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2012. – Т. 11. – С. 248-260.
Keywords: геополітична обстановка; конфліктогенні та терогенні фактори; новий світовий порядок; геополитичкеская обстановка; конфликтогенные и терогенные факторы; новый мировой порядок; geopolitical situation; conflicts and terohenni factors; new world order